Arrowhead design ultrasonic tip as a supplementary tool for canal debridement. (7th November 2019) - De‐Deus, G.; Simões‐Carvalho, M.; Belladonna, F. G.; Cavalcante, D. M.; Portugal, L. S.; Prado, C. G.; Souza, E. M.; Lopes, R. T.; Silva, E. J. N. L.
Abstract: Aim: To investigate the shaping and cleaning performance of the Clearsonic ultrasonic tip as a supplementary tool during the preparation of long oval‐shaped root canals through micro‐computed tomographic (micro‐CT) imaging technology. The Reciproc M‐Wire R40 instrument was used as a reference instrumentation technique for comparison. Methodology: Twenty mandibular incisors with single, straight and long oval‐shaped canals were selected and pair‐matched by micro‐CT scanning. The root canals were prepared with Reciproc R25 and R40 instruments, scanned again in a micro‐CT device and randomly allocated into one of the two experimental groups ( n = 10), according to the supplementary debridement protocol used: Clearsonic or Reciproc R40 used in a brushing motion against buccal and lingual walls. Noninstrumented canal areas, accumulation of hard‐tissue debris (AHTD) and volume of removed dentine were assessed using micro‐CT imaging following the supplementary debridement protocols. Data were analysed statistically in two phases using a t‐test with a significance level of 5%. Results: In phase‐1, there was a significant similarity between the samples regarding the evaluated micro‐CT baseline parameters ( P > 0.05), validating the anatomical similarity between the tooth pairs. In phase‐2, there was a significant difference between the groups for canal volume, surface area, noninstrumented root canal walls and the amount of removed dentine for both absolute and percentage values ( P < 0.05), but not for AHTD ( P = 0.759). Conclusions: The Clearsonic tip outperformed the Reciproc R40 instrument as a supplementary debridement protocol as it was associated with significantly greater reduction of noninstrumented root canals walls and consequently a larger amount of removed dentine. Both groups performed similarly regarding the AHTD.